Hubungan Hukum Antara Pemerintah Dengan Badan Usaha Swasta Dalam Berbagai Pola Kontrak Kerjasama Pengusahaan Pertambangan - Abrar Saleng (Fakultas Hukum Universitas Islam Indonesia, 2000)
In a welfare state, the administration of non-governing functions requires that there have been an equal relation between the legal subjects. The relations probably arise from various legal civil actions taken by the government bodies, particularly those bodies withstatus of legal entity. The civil legal between the govemment with civil of legal entity are directed at achieving the highest welfare of the community. The pattern of cooperation contract based on the mining exploitation in juncture of foreign investment according tothe meaning and substance of the rights of the state control shall be production sharing contract.